Territorial transformations of the North Oasis perceived by wine growers: an approach from the irrigation water = Transformaciones territoriales del Oasis Norte percibidas por productores vitícolas: un acercamiento desde el agua de rieg - Perez, Martin Alberto; Dalmasso, Caterina; Silva Colomer, Jorge; Del Barrio, Lucia; Bres, Emilce Susana; Russo, Fiorella; Van Den Bosch, María Eugenia; Lettelier, María Dolores (GiESCO, 2020)
This work is part of the INTA-COVIAR project Analysis of the social capital of the vine growers of the Northern Oasis of Mendoza: impact on the territory and spatial planning. One of the goals of this study is to know the perception of the territorial transformations and their impact on viticultural activity, for which the bourdiano social capital approach was used. It was decided to implement a qualitative research methodology. Workshops were held with key informants to identify relevant territorial transformations. Subsequently, interviews were carried with two types of producers. The study area was sectorized in order to visualize the differential perceptions of these transformations. A set of problems on the water resource raises from the analysis of the interviews carried out so far. This problems are related to the use for irrigation and how the provision and the quality are affected by territorial changes, highlighting a concrete link between the transformations and the viticultural activity. As firsts results we find out that transformations such as the urban sprawl and the changes of the infrastructure irrigation are perceived with greater relevance in the impact on irrigation water. However, climate change and increased abandonment of plots, identified in institutional workshops, are not perceived as relevant or influential in irrigation. These social perceptions of irrigation water allows to elucidate, in part, the impact of the current transformations and the formal and informal social relationships that are generated around them.